SISTEM MONITORING DAN PERINGATAN KETINGGIAN AIR KOLAM IKAN DENGAN SENSOR HC-SR04 - Muhammad Rafli; Nonot Wisnu Karyanto (Melek IT : Information Technology Journal, 2022)
The Fish Pond Water Level Monitoring and Warning Tool works automatically, the creation of this tool will help Tilapia fish farmers in running their business, this tool will detect the fish pond water level with the HC-SR04 sensor and will give a warning in the form of an Alarm and also get a notification in the form of Twitter, so that fish farmers will get information quickly. With this tool, Tilapia farmers do not need to measure the water level directly and measure one by one if there are many fish ponds. This tool is set automatically when the water level of the fish pond changes according to changes in the surrounding environment. The creation of a fish pond water level monitoring and warning system works automatically through several stages. 1) System planning; 2) Needs analysis; 3) System design; 4) Program coding; 5) Testing; 6) The test results went smoothly. Keywords : Monitoring,HC-SR04, Tilapia fish pond